2020
DOI: 10.1159/000510106
|View full text |Cite
|
Sign up to set email alerts
|

Autosomal Dominant Frontotemporal Lobar Degeneration in a Filipino Family with Progranulin Mutation

Abstract: <b><i>Background:</i></b> Compared to Western populations, familial frontotemporal lobar degeneration (FTLD) is rare among Asians. Progranulin (GRN) gene mutation, which is a major cause of FTLD, is likewise rare. We present a family with FTLD from the Philippines with an autosomal dominant pattern of inheritance and GRN mutation and briefly review reports of GRN mutations in Asia. <b><i>Case Presentation:</i></b> The proband is 66 years old with progressive nonf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…We observed atrophy and hypometabolism in the left frontal, temporal, and parietal lobes in our patient, which is consistent with the asymmetric atrophy reported in GRN mutation carriers [25][26][27]. The white matter hyperintense signal in our patient has also been previously reported [20,28]. Amyloid and tau PET were negative, although one case of FTD with GRN mutation in the literature had TAR DNA-binding protein 43 (TDP-43) protein inclusions [29].…”
Section: U N C O R R E C T E D a U T H O R P R O O Fsupporting
confidence: 91%
See 1 more Smart Citation
“…We observed atrophy and hypometabolism in the left frontal, temporal, and parietal lobes in our patient, which is consistent with the asymmetric atrophy reported in GRN mutation carriers [25][26][27]. The white matter hyperintense signal in our patient has also been previously reported [20,28]. Amyloid and tau PET were negative, although one case of FTD with GRN mutation in the literature had TAR DNA-binding protein 43 (TDP-43) protein inclusions [29].…”
Section: U N C O R R E C T E D a U T H O R P R O O Fsupporting
confidence: 91%
“…GRN mutations are rare in China [7], with a prevalence of just 1.2%-2.6% [15][16][17][18][19], and have been infrequently reported in other Asian countries including Japan, Philippines, India, and Korea (where they have never been observed) [20][21][22][23][24]. In contrast, GRN mutations are common in Western countries, accounting for 34.6% of mutations in patients with FTD in Western countries [25].…”
Section: U N C O R R E C T E D a U T H O R P R O O Fmentioning
confidence: 99%
“…Most studies demonstrated the concordance between structural MRI and FDG-PET in MAPT (43,45), GRN (84,85), and C9orf72 (74, 77) mutation carriers. However, controversy still existed regarding the earlier or more sensitive biomarkers (43,45,77).…”
Section: Orf _fdg-petmentioning
confidence: 95%
“…Heterozygous loss-of-function (LOF) mutations in granulin ( GRN ) gene leading to progranulin (PGRN) happloinsufficiency have been identified as a major cause of familial frontotemporal lobar degeneration with TDP-43 accumulation (FTLD-TDP) [ 1 , 2 , 3 , 4 , 5 , 6 ]. FTLD-TDP patients exhibit behavioral changes and language difficulties associated with the neuronal death in the frontal and temporal lobar brain cortex.…”
Section: Introductionmentioning
confidence: 99%